Peran Brand Awareness dalam Memediasi Review Beauty Influencer Terhadap Keputusan Pembelian - Andika Saputra; Muh. Rizal S; Siti Nuridah; Syah Abadi Mendrofa; Farida Akbarina (CV. Ulil Albab Corp, 2024)
The purpose of this study was to analyze the effect of beauty influencer reviews on purchasing decisions mediated by brand awareness of Something products in Solo City. This research was conducted in Solo City, with a total of 110 respondents who had purchased Something products and were active users of social media, using a purposive sampling method. Data collection was carried out by filling out a questionnaire via the Google form. The data obtained were analyzed using path analysis techniques (path analysis). The results showed that beauty influencer reviews had a positive and significant effect on brand awareness of Something products in Solo City. Reviews of beauty influencers have a significant positive effect on purchasing decisions for Something products in Solo City. And brand awareness as a mediating variable is able to influence beauty influencer reviews on purchasing decisions for Somethinc products in Solo City. The implication of this research is the need for the Something brand effort to use other beauty influencers that have been widely trusted by the public to review newly released products, so as to be more able to convince consumers that Somethinc products have real quality.